1951
DOI: 10.1111/j.1365-2621.1951.tb17358.x
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH OF BACTERIA ASSOCIATED WITH FOOD POISONING EXPERIMENTALLY INOCULATED INTO DEHYDRATED MEAT1

Abstract: The problems involved in the production and distribution of dehydrated meats have received attention recently under the Emergency Meat Dehydration Investigations, sponsored by the U. S. Department of Agriculture. The chemcial composition and nutritive value of dehydrated meat have been thoroughly investigated, Orent -Keiles, Hewston, and Butler (1946), Hoagland andSnider (1946), andHankins, Ernst, and Kauffman (1946). Rehydration problems were studied by Hankins and Hetzer (1947), and packaging research was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1951
1951
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…It has been previously observed in the case of dehydrated meat that growth and toxin production of C . botulinum occurred when the moisture content was 40% but not 30% (9). The bread had approximately 34% moisture when prepared b y the new formula as compared with 37% moisture in the old formula.…”
Section: Discussionmentioning
confidence: 90%
“…It has been previously observed in the case of dehydrated meat that growth and toxin production of C . botulinum occurred when the moisture content was 40% but not 30% (9). The bread had approximately 34% moisture when prepared b y the new formula as compared with 37% moisture in the old formula.…”
Section: Discussionmentioning
confidence: 90%
“…The expectation that other strains will behave similarly is strengthened by considering the results obtained by Segalove and Dack (1951). These authors studied the growth of another enterotoxin-producing strain (No.…”
Section: Discussionmentioning
confidence: 99%
“…Observations on staphylococci have shown that they generally tolerate rather higher solute concentrations than most other bacte;ia, and this has formed the basis of media used for enrichment and isolation of staphylococci as proposed by Chapman (1946). Segalove and Dack (1951) reported the growth of various food-poisoning bacteria on dried meat at different water contents. They found that a food-poisoning strain of S. aureus grew at rather lower water contents than the other organisms tested.…”
Section: Introductionmentioning
confidence: 99%
“…The latter solution has an aw close to 0.95. Segalove and Dack (1951) inoculated S. enteritidis into dried meat with various water contents for which the approximate corresponding aw's have been deduced by Scott (1953). At 50 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…NaCl. In experiments with dried meat adjusted to various water contents Segalove and Dack (1951) reported that a strain of S. enteritidis required greater amounts of water for growth than Staphylococcus aurem or an alphahaemolytic-type Streptococcus.…”
Section: Introducrionmentioning
confidence: 99%